مدى مشروعية الاستفادة من الخلايا الجذعية من منظور الفقه الإسلامي والقانون الطبي - يخلف، عبدالقادر Yakhlef, Abdulqader; خضراوي، الهادي (جامعة الجزائر1 بن يوسف بن خدة, 2017)
Medical developments are receiving a great deal of importance now days, mainly in the field that deals with the exploitation of stem cells because they play a significant role in treating the incurable diseases and serve as an alternative to organ transmission and transplantation. Consequently, this research paper aim sat exploring the extent of the legality of the stem cells’ exploitation regarding the Islamic jurisprudence and the Algerian medical and comparative law to explore if they cope with the actual developments or not with the target of filling the gap and solving the problems that may prevent the application of these legal texts.
يشهد العالم في وقتنا الحالي اهتماما بالغا بالتطورات الطبية وبالأخص في مجال الاستفادة من الخلايا الجذعية وذلك نظرا للدور الهام الذي تلعبه هذه الخلايا في علاج الأمراض المستعصية وكبديل عن نقل وزراعة الأعضاء. ولهذا جاءت هذه الدراسة للبحث عن مدى مشروعية الاستفادة من الخلايا الجذعية خاصة أنها قد تصطدم مع مبدأ عدم المساس والتعامل بجسم الإنسان، وهذا كله في ضوء الاجتهاد الفقهي الإسلامي ونصوص القانون الطبي الجزائري والمقارن وإظهار مدى مواكبتها لمثل هذه التطورات الطبية قصد الوصول إلى سد الفراغ القانوني وحل الإشكالات التي قد تعتري تطبيق هذه النصوص القانونية.
Keywords: القانون الطبي -- الخلايا الجذعية -- زراعة الأعضاء -- نقل الأعضاء -- الفقه الإسلامي